![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a.3-(-12+3)+x=x-(-12-10)
<=> 3+9+x=x+22
<=>x-x=22-3-9
<=> 0x=10
b,2-x=14-(x+4)
<=>2-x=14-x-4)
<=>x-x=14-4-2
<=>0x=8
c.x-12=14+(6-x)
<=>x-12=14+6-x
<=>x+x=14+6+12
<=>0x=32
![](https://rs.olm.vn/images/avt/0.png?1311)
a
12 * 13 * 14
= 156 * 14
= 2184
b
67 * 12 +33 * 12
= (67 + 33) * 12
= 100 * 12
= 1200
c
100 * 12 + 100 * 88
= (12+88) * 100
= 100 * 100
= 10000
a . 12 x 13 x 14 b) 67 x 12 + 33 x 12 c) 100 x 12 + 100 x 88
= 156 x 14 = ( 67 + 33 ) x 12 = 100 x ( 12 + 88 )
= 2184 = 100 x 12 = 100 x 100
= 1200 = 10000
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có :
= 2.[1/10.12+1/12.14+1/14.16+...+1/x.(x+2)] = 19/400 = 2/10.12+2/12.14+2/14.16+...+2/x.(x+2) = 19/400
Mà 2/10.12=1/10-1/12
2/12.14=1/12-1/14
............................................
= 1/10-1/12+1/12-1/14+...+1/x-1/x+2 = 19/400
= 1/10-1/x+2 = 19/400
=>1/x+2 = 1/10-19/400 => 1/x+2=21/400
![](https://rs.olm.vn/images/avt/0.png?1311)
( 2x + 1 / 2 ) * ( 3 / 4 - x ) = 0
=> 2x + 1 / 2 = 0 hoặc 3 / 4 - x = 0
2x = - 1 / 2 x = 3 / 4
x = - 1 / 4
Vậy x = -1 / 4 hoặc x = 3 / 4
2 / 10 * 12 + 2 / 12 * 14 + 2 / 14 * 16 + ... + 2 / 48 * 50
= 1 / 10 - 1 / 12 + 1 / 12 - 1 / 14 + 1 / 14 + 1 / 16 + .... + 1 / 48 - 1/ 50
= 1 / 10 - 1 / 50
= 2 / 25
Tìm x : \(\left(2x+\frac{1}{2}\right)\left(\frac{3}{4}-x\right)=0\)
\(\Rightarrow\orbr{\begin{cases}2x+\frac{1}{2}=0\\\frac{3}{4}-x=0\end{cases}\Rightarrow\orbr{\begin{cases}x=\frac{-1}{2}\\x=\frac{3}{4}\end{cases}}}\)
Tính nhanh : \(\frac{2}{10.12}+\frac{2}{12.14}+...+\frac{2}{48.50}\)
\(=2\left(\frac{1}{10.12}+\frac{1}{12.14}+...+\frac{1}{48.50}\right)\)
\(=2.\frac{1}{2}\left(\frac{1}{10}-\frac{1}{12}+\frac{1}{12}-\frac{1}{14}+...+\frac{1}{48}-\frac{1}{50}\right)\)
\(=\frac{1}{10}-\frac{1}{50}\)
\(=\frac{2}{25}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(A.4-\left(12-17\right)=17-\left(x-4+15\right)\)
\(\Leftrightarrow4-\left(-5\right)=17-\left(x+11\right)\)
\(\Leftrightarrow9=17-x-11\)
\(\Leftrightarrow6-x=9\)
\(\Leftrightarrow x=6-9\)
\(\Leftrightarrow x=-3\)
\(B.14-\left(12-x\right)=4-\left(15-13\right)\)
\(\Leftrightarrow14-12+x=4-2\)
\(\Leftrightarrow2+x=2\)
\(\Leftrightarrow x=2-2\)
\(\Leftrightarrow x=0\)
14 - ( x - 12 ) : 12 = 12
=> ( x - 12 ) : 12 = 14 - 12 = 2
=> x - 12 = 2 x 12 = 24
=> x = 24 + 12
=> x = 36
14-x+12=12.12
14-x+12=144
14-x=144-12
14-x=132
x=14-132
x=-118
vậy x=-118